The application of generalising judgements and their influence on the images of selected Polish columnists (a constructivism-focussed quantitative and qualitative approach) - Barańska-Szmitko, Anna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The goal of the text was to indicate the image characteristics of an author of a verbal expression which were communicated through expressing generalising judgements, and to establish the difference between such generalisations depending on the given image characteristic. I used constructivism as the leading theory. In terms of methodology, I applied mixed methods: quantitative (quasi-experiment) and discourse analysis. The analysis indicated that generalisations are used for communicating the characteristics of: intelligent, critical, bluntly states her/his bold judgements, insightful, writes in an interesting way, realist, frank, while the receivers assign some of the characteristics depending on the degree of evaluation emphasis, reference to a taboo, utilisation of negation, and expressions using the 1st person plural.